Application of Factorial Design Analysis to Control Bisphenol A MIP fabrication - C. K. M., Faizal; Shareena, Mohd Sharif (2011)
A key issue in the synthesis of molecular imprinted polymer nanoparticles is the identification and optimization of the main factors affecting the material structure and size. This paper describe an experimental design approach to synthesis bisphenol A molecular imprinted polymer nanoparticles (BPA-MIP NPs) aimed at analysis of the relationship of four selected parameters: the polymerisation temperature, agitation rate, cross-linker to solvent ratio, and percentage of initiator. The results presented demonstrate the importance of keeping the right balance between these various parameters of polymerisation conditions which are approximately 60oC, 100rpm, 65% solvent ratio and 1% initiator, respectively. Generally, it can be concluded that MIPs should be synthesized using enough heating, adequate agitation, low concentration of initiator and with a bit higher amount of solvent. Such procedure is proven as time and cost effective, and also can be used as a general tool in the preparation of MIP NPs for different target molecules.